New institutional economics as a tool for improving transaction governance in the Polish fruit sector - Xavier Gellynck; Ewa Halicka; Jacques Viaene (Journal for East European Management Studies, 2002)
It was expected that price liberalisation and privatisation in transition economies would spontaneously result in the necessary institutions that underpin Western market economies. However, these institutions are not developing as expected. The objective of the paper is to understand why these institutions are not developing in the Polish fruit sector. It mainly focuses on transaction cost economics and its link with economic development. Based on interviews with all participants in the Polish fruit chain, hold-up problems are identified and solutions proposed. – – Es wurde erwartet, dass Preisliberalisierung und Privatisierung in den Transformationsländern zu den Institutionen führen würden, die auch die westlichen Marktwirtschaften untermauern. Diese Institutionen entwickeln sich jedoch nicht wie erwartet. Dieser Beitrag soll zeigen, warum sich diese Institutionen in der polnischen Obstbranche nicht entwickeln. Hauptsächlich fokussiert er auf die Transaktionskostenökonomie und deren Einfluss auf die Wirtschaftsentwicklung. Basierend auf Interviews mit Akteuren der polnischen Obstbranche werden Probleme identifiziert und Lösungen vorgeschlagen.
Keywords: 650